Strategi Promosi Produk Kerajinan Daur Ulang Sampah Untuk Menarik Minat Beli Masyarakat di Bank Sampah Sri Rejeki - Habibah Habibah; Afrida Yani; Lyandra Aisyah Margie; Fitria Anggraini Rostianti (S1 Accounting Program, Universitas Pamulang, 2020)
This community service has a general goal to help partners set a strategy for promoting waste recycling handicraft products so as to attract public buying interest, an appropriate promotional strategy will greatly assist partners in marketing handicraft products. The theme of this PKM is Promotion Strategy, by involving lecturers and resource persons Lecturers in the Accounting Study Program from Pamulang University. The results of the PKM implementation carried out on 18, 19 and 20 June 2020 were adding knowledge in the field of marketing, especially about promotion strategies from the participants of the Sri Rezeki Waste Bank Management group in Benda Baru, South Tangerang, Banten. The response of the participants was very good and happy because it was very helpful in learning about the promotion strategy. The suggestion that was conveyed was the PKM activities in the future to be carried out continuously so that the participants would always get guidance in conducting promotional strategies so that handicraft products could attract people's buying interest. To the community to be more enthusiastic in collecting waste because it can provide high economic value.